Enhancement of Salt Rejection and Water Flux by Crosslinking-Induced Microstructure Change of N-substituted Polybenzimidazole Membranes. Issue 1745 (16th September 2015) - Aiba, Motohiro; Tokuyama, Takahiro; Matsumoto, Hidetoshi; Tomioka, Hiroki; Higashihara, Tomoya; Ueda, Mitsuru
ABSTRACT: Crosslinked or non-crosslinked ultrathin semipermeable membranes based on the N -butylated and N -butylsulfonated polybenzimidazole (BPBI and BSPBI) were successfully prepared by spin-coating method. Structural characterization by FTIR and WAXD revealed that the N -substitution and the crosslinked structure of PBI suppressed the hydrogen bonding and increased the d -spacing. Furthermore, positron annihilation lifetime spectroscopy (PALS) clearly showed the pore radius change from 0.27-0.29 nm to 0.33 nm by crosslinking. As a result, the enhancement of water flux and NaCl rejection was achieved by the crosslinking of the BPBI and BSPBI. Especially, the crosslinked N -butylsulfonated PBI (CL-BSPBI) membrane significantly improved not only salt rejection but also water flux (NaCl rejection : 46 %, water flux : 22.1 L m -2 h -1 ) compared to those of non-crosslinked BSPBI one (NaCl rejection : 11 %, water flux : 1.88 L m -2 h -1 ) due to both the Donnan effect and the formation of larger pores in the membrane, respectively.